2016
DOI: 10.2174/1574887111666160330121851
|View full text |Cite
|
Sign up to set email alerts
|

What is the Current Role of Immunotherapy for Colon Cancer?

Abstract: Colon cancer is a leading cause of cancer related mortality. Until very recently the only existing options that medical oncologists had to treat metastatic colon cancer were a combination of chemotherapy, anti-EGFR and anti-angiogenic agents. We currently have the first proof that immune therapies could be an effective approach to battle colorectal cancers that carry a mismatch repair machinery deficient phenotype. It is expected that as our knowledge of the different mechanisms of immune-resistance grows, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In human cancer, involvement of tumor infiltration of T cells to obtain an antitumor immune response is considered to be predictive factors, associated with long-term survival of patients. 24,38 In our strategy, RFA and local combination therapy showed a strong increase of TILs in the distant tumors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In human cancer, involvement of tumor infiltration of T cells to obtain an antitumor immune response is considered to be predictive factors, associated with long-term survival of patients. 24,38 In our strategy, RFA and local combination therapy showed a strong increase of TILs in the distant tumors.…”
Section: Discussionmentioning
confidence: 76%
“…We evaluated lymphoid cells density in distant liver metastases by automatic count, as described by Allard et al 24 Our data showed low lymphocyte densities of CD3, CD4 and CD8 on the patient tumors ( Figure 1(a)). Furthermore, lymphocyte infiltration analysis showed similar patterns for all markers in both groups; characterized by a small increase of TILs on the tumor front ( Figure 1(b)).…”
Section: Rfa Treatment Alone Did Not Increase Tils In Patients' Colormentioning
confidence: 99%
“…In the gastrointestinal tract they are especially abundant in the neuroendocrine cells of the mucosa, suggesting a role as a gut hormone for this peptide. Previous studies confirmed that both AM and PAMP regulate many physiological and pathological conditions in the gut (Galanternik et al, 2016 ). Furthermore, AM and PAMP also act as antimicrobial peptides, constituting a defense mechanism against pathogenic bacteria (Allaker et al, 1999 ).…”
Section: Introductionmentioning
confidence: 58%
“…The improving quality of life, changes in eating habits and pollution of the environment have resulted in increased incidence of colon cancer in recent years [3] . Surgery, chemotherapy, radiotherapy and immunotherapy are the four major therapeutic modalities [4] . Although the survival rate of colon cancer patients has increased thanks to advanced and improved early diagnostic and therapeutic strategies, the five-year survival rate is only about 50% worldwide [5] .…”
Section: Backgroudmentioning
confidence: 99%